The Apocalypse ; v. 2 a series of special lectures on the Revelation of Jesus Christ with revised text - Seiss, Joseph Augustus, b.1823 (New York, NY Charles C. Cook, 1917)
Contents : v. 2 : Chapters 8-13
Keywords: Bible N.T. Revelation VIII-XIII -- commentaries